Coconut oil based microemulsion formulations for hair care product application - Safiah Mohamad Ja’afar,; Rozida Mohd. Khalid,; Rizafizah Othaman,; Wan Nur Aini Wan Mokhtar,; Suria Ramli, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Coconut oil in microemulsion is a better option than conventional practice since it can incorporate bioactive ingredients with a stable control release property, especially for hair care products. This work aims to develop microemulsion systems based on coconut oil with the addition of Tween 20, Tween 40, and Tween 80 as non-ionic surfactants (S), and propylene glycol as a co-surfactant (CoS). The determination of microemulsion regions in the ternary phase diagram was carried out by water titration method and the properties of the microemulsion were analysed. Based on the results, the microemulsion system of coconut oil with Tween 80 produced the largest microemulsion region compared to Tween 40 and Tween 20. Microemulsion systems of coconut oil/Tween 80 with the addition of propylene glycol with the ratio of S/CoS at Km = 3:1, 2:1, and 1:1 resulted in a decrement of microemulsion regions compared to using merely Tween 80. The microemulsion system of coconut oil/Tween 80/water at the ratio of oil: surfactant = 1:9 was chosen for further characterisations. Viscosity and electrical conductivity studies showed that the microemulsion system was water-in-oil (w/o) type as there was no phase transition to bicontinuous (BC) or oil-in-water (o/w) type due to low percentage of water content. Stability studies showed that the microemulsion system remained clear and stable at 25 and 40°C upon one-month storage except at 4°C where the system became cloudy and turbid. For particle size analysis, the microemulsion system possessed particle size less than 100 nm.